Atrioventricular Valve Repair in Single Ventricle Physiology: Timing Matters - Leonardo Augusto Miana; Valdano Manuel; Aida Luísa Turquetto; H Issa; Gustavo Pampolha Guerreiro; Luiz Fernando Canêo; Fábio Biscegli Jatene; Marcelo Biscegli Jatene (2019)
Objectives: Atrioventricular valve (AVV) regurgitation in patients with single ventricle (SV) physiology severely impacts prognosis; the appropriate timing for surgical treatment is unknown. We sought to study the results of surgical treatment of AVV regurgitation in SV patients and evaluate risk factors for mortality. Methods: Medical records of 81 consecutive patients with moderate or severe AAV regurgitation who were submitted to AVV repair or replacement during any stage of univentricular palliation between January 2013 and May 2017 were examined. We studied demographic data and perioperative factors looking for predictors that might have influenced the results. Binary logistic regression was used to assess the impact on postoperative ventricular dysfunction and mortality. Results: Median age and weight were seven months (interquartile range [IQR]: 3-24) and 5.2 kg (IQR: 3.7-11.2), respectively. Seventy (86.4%) patients underwent AVV repair, and 11 (13.6%) patients underwent AVV replacement. There was an association between AVV repair effectiveness and timing of intervention ( P = .004). Atrioventricular valve intervention at the time of initial surgical palliation was associated with more ineffective repairs ( P = .001), while AVV replacement was more common between Glenn and Fontan procedures ( P = .004). Overall 30-day mortality was 30.5% (25 patients). In-hospital mortality was 49.4%, and it was higher when AVV repair was performed concomitant with initial (stage 1) palliation (64.1% vs 35.7%; P = .01) and when an effective repair was not achieved (75% vs 41%; P = .008). Multivariable analysis identified timing concomitant with stage 1 palliation as an independent risk factor for mortality ( P = .01); meanwhile, an effective repair was a protective factor against in-hospital mortality ( P = .05). Conclusion: Univentricular physiology with AVV regurgitation is a high-risk group of patients. Surgery for AVV regurgitation at stage 1 palliation was associated with less effective repair and higher mortality in this initial experience. On the other hand, effective repair determined better outcomes, highlighting the importance of experience and the learning curve in the management of such patients.